Supervisi Klinis Tingkatkan Kemampuan Perencanaan, Pelaksanaan, dan Evaluasi Pembelajaran Efektif di Gugus Melati - Yennie Damayanti Puspasari; Esti Setiawati (Proceedings Series on Social Sciences & Humanities, 2022)
This study aims to describe the state of teacher performance in the upper grades of the Gugus Melati Elementary School Korwil Banyuurip in semester 1 of the 2021/2022 academic year. Supervisor observation data obtained by researchers when supervising learning. This type of research is School Action Research (PTS). The data collection method used is using the method of observation, monitoring, questionnaires, and instruments that describe the improvement of teacher learning. Researchers describe teacher performance in the form of a grid to get a picture of the condition of teacher performance both before the implementation of clinical supervision and after clinical supervision of effective learning is carried out. The data of this study were analyzed using a simple quantitative approach with the percentage technique. The results showed: (1) The initial condition of the learning device completeness score was 74.8% with a very good classification reaching 19%. Cycle I score 80.8% with the number of very good classification 23.8%. In the second cycle the score became 86.4 with the number of very good classifications reaching 38.1%. At the end of the third cycle the score was 96.3 with a very good number of 95.2 classifications. (2) The initial condition score of the aspect of the ability to implement learning is 74.8% with a very good classification reaching 0%. Cycle I scored 78% with a very good classification being 14.3%. In the second cycle, the score was 86.4 with the number of very good classifications reaching 38.1%. At the end of the third cycle the score was 89.4% with a very good classification of 85.7%. (3) The initial condition score for learning evaluation ability is 73.18% with a very good classification reaching 0%. Cycle I scored 79.2% with a very good classification of 23.8%. In the second cycle, the score was 83.5% with the number of very good classifications reaching 43.9%. At the end of the third cycle the score was 91.1% with a very good classification of 81.0%.